Effects of Nigella sativa and silver sulfadiazine on burn wound healing in rats - Yaman, I.; Durmus, A. S.; Ceribasi, S.; Yaman, M. (Czech Academy Agricultural Sciences, 2010)
This experiment was conducted in order to compare the effects of Nigella sativa (NS) and silver sulfadiazine (SSD) cream on healing of burn wounds in rats. Fifty four adult, male Wistar-albino rats were divided into three groups of equal numbers. A burn was generated on the backs of all the rats. The burned areas in the first, second and third groups were covered with daily cold cream (control), SSD cream and NS cream (50% NS oil + 50% cold cream), respectively. Four, nine, and 14 days later, the rats were sacrificed and the burned skin tissue samples were collected for histopathological examinations. Histopatological evaluations on the 4(th), 9(th) and 14(th) days showed burn healing to be better in the NS and SSD groups with respect to the control group. Wound healing was significantly different among the groups at 4(th), 9(th) and 14(th) days (P < 0.001). In conclusion, application of NS and SSD cream are effective in healing burn related skin wounds in the rat model.
Keywords: Nigella sativa; silver sulfadiazine; burn; rat